Konsumen Muslim: Pengetahuan Produk Halal dalam Keputusan Pembelian Makanan - Musthofa, Ariezal; Buhanudin, Burhanudin (el-Jizya : Jurnal Ekonomi Islam, 2021)
Being Muslim doesn’t guarantee that someone has adequate halal knowledge. The variety of extracting halal knowledge of Muslim consumers is important because it becomes the basis for their purchase decisions. This paper aims to explore the halal knowledge of Muslim consumers and exprimentally confirm the range of the knowledge. The exploration was carried out through a Focus Group Discussion (FGD). Then, an experiment to 239 Muslim consumers was conducted to confirm the findings of FGD. FGD found participants with a minimum level of halal knowledge use the halal logo Majelis Ulama Indonesia (MUI) or the Indonesian Ulema Council, as the basis for determining the halalness of a product in their purchase decisions. Furthermore, FGD found participants with good halal knowledge use other considerations (for example, the process of slaughtering animals, mentioning the name of Allah SWT) when they do not find the MUI halal logo in determining the halalness of a product. The experiment confirms the different levels of their halal knowledge. The findings imply that products need to include halal logo from MUI, not from other sources, to ease Muslim consumers make buying decisions.